PENGARUH ALAT PERAGA BENDA KONKRIT TERHADAP MOTIVASI DAN KEMAMPUAN BERFIKIR KRITIS MATEMATIKA - Arifin, Zainal (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to determine the effect of concrete objectzteaching aids on students' motivation and critical thinkingzin mathematics. This quantitative study used aznonequivalent controlzgroupzdesign. Thezpopulation iszfourth grade studentszofzUPTD SDzNegerizParseh 3 Bangkalan, with a sample of 40 students in class IV-A and IV-B. The non-test instrument used was in the form of a questionnairezand a test in the form ofzpretest and posttest questions. While the analysis tests are validity tests by material experts, expert reliabilityztests, normality tests, homogeneityztests and IndependentSample T-tests. The results of the test of differences in motivation to learn mathematics on puzzle props and snakes and ladders teaching aids for grade 4 at UPTD SD Negeri Parseh 3 can be seen in table 1. whichzobtained a significancezvalue of 0.043 < 0.05zso thatzthe datazcan be assumed tozhave different variances. There are differences in mathematical critical thinking in puzzle props and snake ladderzprops for grade 4 at UPTD SD Negeri Parseh 3 can be seen in table 2. which obtainedza significancezvalue ofz0.000 < 0.05zso thatzthe data can bezassumed to have different variances.